Lower Limb Muscle Synergies During Normal Gait and Obstacle Avoidance in Humans - Morin, Evelyn (CMBES Proceedings, 2007)
Synchronous muscle synergies were extracted from muscle activation patterns in six lower limb muscles as subjects avoided an obstacle (a real or virtual hole in the pathway) during walking. These synergies were compared to synergies previously extracted during normal walking [5]. Some reorganization in the synergy patterns during obstacle avoidance was found. The alterations can be explained in terms of maintaining stability while avoiding an obstacle